2019
DOI: 10.1101/781559
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

dotdotdot: an automated approach to quantify multiplex single molecule fluorescent in situ hybridization (smFISH) images in complex tissues

Abstract: ABSTRACTMultiplex single-molecule fluorescent in situ hybridization (smFISH) is a powerful method for validating RNA sequencing and emerging spatial transcriptomic data, but quantification remains a computational challenge. We present a framework for generating and analyzing smFISH data in complex tissues while overcoming autofluorescence and increasing multiplexing capacity. We developed dotdotdot ( Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 70 publications
(82 reference statements)
1
18
0
Order By: Relevance
“…Similarly, the classical D2-MSN marker PENK was enriched in the large population of D2.2 MSNs, but depleted in the smaller population of D2.1 MSNs ( Figure S1). Expression of these neuropeptides in D1 and D2 MSN subclasses was confirmed using single molecule fluorescent in situ hybridization (smFISH) with 4-plex RNAscope technology (Maynard et al, 2020b), and showed that the majority of D2-expressing cells in the NAc belonged to the D2.2 class (86.8%, Figure S1).…”
Section: Identification Of Refined Medium Spiny Neuron Subpopulationsmentioning
confidence: 96%
See 1 more Smart Citation
“…Similarly, the classical D2-MSN marker PENK was enriched in the large population of D2.2 MSNs, but depleted in the smaller population of D2.1 MSNs ( Figure S1). Expression of these neuropeptides in D1 and D2 MSN subclasses was confirmed using single molecule fluorescent in situ hybridization (smFISH) with 4-plex RNAscope technology (Maynard et al, 2020b), and showed that the majority of D2-expressing cells in the NAc belonged to the D2.2 class (86.8%, Figure S1).…”
Section: Identification Of Refined Medium Spiny Neuron Subpopulationsmentioning
confidence: 96%
“…After amplification steps (AMP1-3), probes were fluorescently labeled with Opal Dyes (Perkin Elmer, Waltham, MA; 1:500) and stained with DAPI (4′,6-diamidino-2-phenylindole) to label the nucleus. Lambda stacks were acquired in zseries using a Zeiss LSM780 confocal microscope equipped with a 63x x 1.4NA objective, a GaAsP spectral detector, and 405, 488, 555, and 647 lasers as previously described (Maynard et al, 2020b). All lambda stacks were acquired with the same imaging settings and laser power intensities.…”
Section: Rnascope Single Molecule Fluorescent In Situ Hybridization (mentioning
confidence: 99%
“…For each subject, a cortical strip was tile imaged at 20x to capture L1 to WM. Following image acquisition, lambda stacks in z -series were linearly unmixed in Zen software (weighted; no autoscale) using reference emission spectral profiles previously created in Zen (Maynard et al, 2019) , stitched, maximum intensity projected, and saved as Carl Zeiss Image " .czi " files.…”
Section: Rnascope Single Molecule Fluorescent In Situ Hybridization (mentioning
confidence: 99%
“…Because it is considered a gold standard for quantifying gene expression with high spatial resolution, we recently established and optimized methods for using multiplex single-molecule fluorescent in situ hybridization (smFISH) in postmortem human brain tissue (Maynard et al, 2019) . However, multiplexing with these technologies is limited, and even for methodologies that can accommodate hundreds to thousands of transcripts simultaneously, molecular crowding within cells leads to fluorescence overlap, which introduces significant microscopy-related issues and computational challenges (Burgess, 2019;Lein et al, 2017) .…”
Section: Introductionmentioning
confidence: 99%
“…Once centers and boundaries of individual cells were isolated, an intensity threshold was set for transcript detection, and watershed analysis was used to split the remaining pixels in each channel into identified transcripts. Custom MATLAB functions 49 were then used to determine the size of each detected transcript (regionprops3 function in Image Processing toolbox), and split unusually large areas of fluorescence into multiple transcripts based on known transcript size. Each transcript was then assigned to a cell based on its position in 3 dimensions; transcripts that were detected outside of the boundaries of a cell were excluded from further analysis.…”
Section: Single-molecule In Situ Hybridizationmentioning
confidence: 99%